Financial Literacy Study of Urban Farmers in Makassar City - Fira Ayu Sasmita; Muhammad Hasan; Citra Ayni Kamaruddin; Nurdiana; Nur Arisah (Quantitative Economics and Management Studies, 2022)
The tendency of people to make purchases without paying attention to financial principles has resulted in people being irrational in buying necessities, especially farmers in farmer women’s group Anggrek. This study aims to examine the level of financial literacy of urban farming entrepreneurs, especially in farmer women’s group Anggrek, Bara – Baraya Village, Makassar District, Makassar City. The research method used is descriptive qualitative, with data collection techniques through observation and interviews. The data analysis technique used in the research is data reduction, the next is data presentation, after that draw conclusions. The informants in this study used purpositive sampling, the informants in this study were 4 people who were farmers at farmer women’s group Anggrek. And to determine the level of financial literacy of urban farming entrepreneurs, especially in the Anggrek Women Farmer Group, there are 4 indicators studied in this study, namely 1) Knowledge of finance 2) Knowledge of Savings and Loans 3) Knowledge of Insurance and 4). Knowledge of Investment. The results of the study explain that the overall level of financial literacy of farmers in farmer women’s group Anggrek still needs to be improved, although knowledge about finance and savings, and loans is quite good, but trust and use of financial institutions, insurance and investment are still very limited. So it is necessary to increase financial literacy for farmers, especially in farmer women’s group Anggrek.